Analisis Perbandingan Perhitungan Re-Order Point - Haryadi Sarjono; Engkos Achmad Kuncoro (Binus Business Review, 2014)
The purpose of this study was to compare the Re-Order point (ROP) between the ongoing policy of the company to the theoretical calculation according to the method of Economic Order Quantity (EOQ) in manufacturing company. The research methodology that is used in this research is the method of quantitative analysis. It is a scientific approach to managerial decision making in which the source data is the primary data obtained directly from resource persons to provide the necessary data. The data is taken from the data the raw materials the company from 2007 to 2012. The results of this study state that the re-order point calculations specific to the year 2012 only, according to the company policy is 34,508 Kg, while according to the calculation method of EOQ is 91 925 Kg. This difference is due to the calculation of safety stock and the use of time while waiting.